Methodical instructions for the implementation of practical work in the discipline "Radiation and electromagnetic safety" - Babenko, Vladyslav; Tykhomyrova, T. S.; Sakun, Antonina (Національний технічний університет "Харківський політехнічний інститут", 2025)
Safety of life is one of the key conditions for the normal functioning of a person both in everyday life and professional activities. Radiation safety and radiation protection measures are a branch of science and practice aimed at preserving people's health when working with sources of ionizing radiation. Ionizing radiation (SIR) sources are widely used in industry, energy, scientific research, and medicine. According to the State Sanitary and Epidemiological Service, about 10 thousand enterprises, institutions, and organizations in Ukraine use various IR sources, including more than 30 thousand radionuclide devices. Working with radioactive substances and SIR is associated with increased risk since, in emergency situations, a person cannot detect radiation using the senses - its presence is recorded exclusively by special measuring devices. Therefore, increasing safety when working with radiation sources requires strict compliance with current regulations, instructions, and safety rules. Radioactive contamination caused by accidents can persist in the environment for long, and decontamination options are limited. In this regard, an essential component of the modern radiation safety strategy, which has gained particular importance after the Chornobyl disaster, is the creation of barriers that prevent the penetration of radioactive substances into the food chain.
Keywords: methodical guidance; practical work; radiation safety; electromagnetic safety; life safety; nuclear safety